Invasion of the scorp-lions : a Monstertown mystery - Hale, Bruce (A Monstertown mystery, 2017)
When a classmate falls into a coma, best friends and monster hunters Carlos and Benny investigate weird noises and smells that are coming through Monterrosa Elementary's classroom vents.